Synthesis and structural investigations of bulky imino- and amido-phosphine palladium dimers - Pascu, S; Anderson, G; Green, M; Green, J; Rees, N; Cowley, A (2006)
The reactions of palladium(II) dimers [Pd2Br2(L1)2] and [Pd2Br2(L2)2] (where L1- is [Ph2PCH{double bond, long}C(Ph)N(2,6-iPr2C6H3)]- and L2- is [Ph2PCH{double bond, long}C(Ph)N(2,6-Me2C6H3)]-) with AgBF4 in a mixture of CH2Cl2 and MeOH give palladium(I) dimers [Pd2(HL1)2][BF4]2 and [Pd2(HL2)2][BF4]2, respectively. These exhibit unusual coordination geometries of the metal centre. Density functional theory (DFT) calculations showed that a phenyl ring of the bridging phosphine is involved in bonding via a delocalised metal-phosphine-phenyl interaction. The remarkable kinetic stability of these palladium(I) species may explain the early termination steps in the CO/ethylene copolymerisation reaction catalysed by Pd(II)-amidophosphines or enolisable Pd(II)-iminophosphines. © 2006 Elsevier B.V. All rights reserved.